(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
Teacher training is an important institutional activity that provides teachers with elements aimed at strengthening didactic, pedagogical and technological references that allow them to better perform their activity. The objective of this work is to compare the teaching evaluation carried out by the students of the dental teaching staff who took the teacher training diploma with teaching staff who did not take it. An online questionnaire is applied to 183 students, blinding which ones took the diploma and which did not. The results are compared using the Mann-Withney U for independent samples with a significance of 0.05. 73.3% of the items show better ratings for teachers with a diploma, so it is concluded that the impact of the diploma was positive.